Defining quantitative parameters and coordinates of the defect signal by acoustic-emission control of cylindrical tanks - A. A. Kuznetsov; V. P. Kulakovskaya (Омский научный вестник)
In this article there is presented the data obtained by researching the acoustic emission signals when controlling the surface defects of sealed tanks. In the process of studies with pressure changes the data on changes in the parameters of the signals recorded by the digital acoustic-emission control system SCAD-16 have been obtained. On the basis of the obtained results the methodology for determining the coordinates of the defects of the tanks using the cylindrical coordinate system has been proposed. The approach proposed in the article makes it possible to reduce the error of determining the coordinates of defects, as compared to the expressions in the case of rectilinear wave propagation on a flat surface.